2001
DOI: 10.1079/pns2001123
|View full text |Cite
|
Sign up to set email alerts
|

Dietary fatty acid modulation of mucosally-induced tolerogenic immune responses

Abstract: Immunological unresponsiveness or hyporesponsiveness (tolerance) can be induced by feeding protein antigens to naïve animals. Using a classical oral ovalbumin gut-induced tolerance protocol in BALB/c mice we investigated the effects of dietary n-6 and n-3 polyunsaturated fatty acids (PUFA) on high-and low-dose oral tolerance (and in non-tolerised animals, i.e. effects of antigen challenge alone) in relation to lymphoproliferative, cytokine and antibody responses. Fish oil rich in long-chain n-3 fatty acids dec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
14
0
2

Year Published

2003
2003
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 67 publications
5
14
0
2
Order By: Relevance
“…A recent clinical study with topically applied hempseed oil has already demonstrated its usefulness in healing mucosal skin wounds after eye, nose and throat surgery (Grigoriev, 2002). This finding is in line with numerous other clinical studies that have demonstrated the utility of EFAs and other PUFAs in healing and immune response (Manku et al, 1982(Manku et al, , 1984Bordoni et al, 1988;Oliwiecki et al, 1991;Sakai et al, 1994;Yu & Björkstén, 1998;Derek & Meckling-Gill, 1999;Harbige et al, 2000;Harbige & Fisher, 2001;Horrobin, 2000;Simopoulos, 2002a,b). The fatty acid profile of hempseed oil is remarkably similar to that of black currant seed oil, which also seems to have a beneficial impact on immunologic vigor (Wu et al, 1999;Barre, 2001).…”
Section: Empirical and Clinical Studies On Hempseed Oilsupporting
confidence: 53%
“…A recent clinical study with topically applied hempseed oil has already demonstrated its usefulness in healing mucosal skin wounds after eye, nose and throat surgery (Grigoriev, 2002). This finding is in line with numerous other clinical studies that have demonstrated the utility of EFAs and other PUFAs in healing and immune response (Manku et al, 1982(Manku et al, , 1984Bordoni et al, 1988;Oliwiecki et al, 1991;Sakai et al, 1994;Yu & Björkstén, 1998;Derek & Meckling-Gill, 1999;Harbige et al, 2000;Harbige & Fisher, 2001;Horrobin, 2000;Simopoulos, 2002a,b). The fatty acid profile of hempseed oil is remarkably similar to that of black currant seed oil, which also seems to have a beneficial impact on immunologic vigor (Wu et al, 1999;Barre, 2001).…”
Section: Empirical and Clinical Studies On Hempseed Oilsupporting
confidence: 53%
“…The main inflammatory mediators produced by these pathways are eicosanoids, PGE 2 and LTB 4 . 30,31 The COX-1 pathway is involved in gut, kidney and blood function and thus its inhibition is undesirable. 32 The high n-3 PUFA content of Lyprinol™ and fish oil may account for their anti-inflammatory properties in the current study.…”
Section: Discussionmentioning
confidence: 99%
“…It is possible therefore that AA accretion, in addition to growth requirements, is linked to thymic programming (education) in relation to autoreactive T cells and tolerogenic mechanisms and the subsequent development of autoimmune and allergic disorders (11,79). In summary, there is therefore much evidence for an essential role for n-6 fatty acids and their oxygenated metabolites in the lymphoid system but not for n-3 fatty acids.…”
Section: Essentiality Of N-6 Pufa For Cells and Tissues Of The Immunementioning
confidence: 99%
“…The Th cytokine pattern also depends on the dose and properties of antigens, site of exposure, and the environment in which the T cells are found, e.g., production of antigen-presenting cellderived IL-12 can direct Th1 responses via induction of IFN-γ (4,6-8). The dietary fatty acid effect on the nutritional microenvironment of the cell should now also be included with the foregoing factors that influence Th cells and their cytokine pattern (9)(10)(11).…”
mentioning
confidence: 99%